Determination of Environmental Sanitation Factors as a Risk Factor for Diarrhea in KaoFe Village, Buton Regency: A Public Health Approach - Anwar Mbolosi; Supaporn Porntrai (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aimed to analyze environmental sanitation factors as determinants of diarrhea incidence in Desa KaoFe, Kecamatan Kadatua, Kabupaten Buton. Methodology: A quantitative analytic study with a cross-sectional design was conducted among 156 randomly selected households from a population of 260 households. Data were collected through structured interviews and direct observation of sanitation facilities. Variables included access to clean water, household latrine availability, solid waste management, wastewater disposal, and diarrhea incidence within the last three months. Data were analyzed using descriptive statistics and Chi-square tests at a 95% confidence level. Main Findings: The prevalence of diarrhea was 31.4%. Households without adequate clean water access accounted for 34.6%, unhealthy or absent latrines 43.6%, inadequate solid waste management 49.4%, and improper wastewater disposal 75.6%. All sanitation variables showed statistically significant associations with diarrhea incidence (p < 0.05). Novelty/Originality of this study: This study provides a multidimensional assessment of sanitation determinants within a small island rural context, demonstrating that wastewater disposal and integrated sanitation deficiencies play a critical role in diarrhea transmission beyond water access alone.